Strength Analysis and Optimization of Impact Crusher Spindle - Wang Shunkai; Ma Fei; Li Yelin; Geng Xiaoguang (Jixie chuandong)
The mechanical model of impact crusher spindle under operating condition is established and static strength of spindle dangerous section is checked by the method of mechanics of materials.The spindle deflection and torsional rigidity are calculated to check whether they met the design requirements or not.Besides,the specific distributions of stress are figured out through FEM method to determine the positions of dangerous points and the factor of stress concentration.Based on the result,the fatigue strength of spindle is calculated.The structure of the spindle is optimized through analysis.Therefore,the stress concentration of some parts is improved,as well as 8% weight reduction of spindle is obtained.